CURRICULUM AND LEARNING METHODS COMPARATIVE STUDY BETWEEN INDONESIA AND IRAN - Juniar, Putri Nabila; Harryson Siregar, Dennis Jovani; Erdiansyah, Wisnu; Koto, Irwan (MEDIA DIDAKTIKA, 2025)
The purpose of this study is to focus on primary and secondary education on the curriculum and learning methods used in Indonesia and Iran. The background of this study is based on the importance of understanding the education system in both countries, considering the differences in culture, religion and education policies that affect the development of curriculum and learning methods. The purpose of this study is to identify the curriculum structure, learning approaches, and similarities and differences in tasks in both countries in improving the quality of education. The research method used is a qualitative comparative study by collecting data through literature research, analysis of formal curriculum documents, and interviews with education experts from Indonesia and Iran. The results of the study show that both countries have curricula that focus on student development and skills, with different focuses. Indonesia focuses on Pancasila education and local wisdom, while Iran emphasizes education based on Islamic values ​​and revolution. While Indonesia’s learning methods tend to be student-centered (student-centered), Iran still has many traditional approaches (teacher-centric). These findings indicate the need to replace the best knowledge and best practices between the two countries to address challenges such as quality lessons and curriculum relevance. The conclusion of this study is that while both countries make significant differences in curriculum and learning methods, there is an opportunity to learn from each other to improve the education system.